Immunomodulatory effects of avian β-defensin 5 in chicken macrophage cell line. (October 2020) - Hong, Yeojin; Lee, Jiae; Vu, Thi Hao; Lee, Sooyeon; Lillehoj, Hyun S.; Hong, Yeong Ho
Abstract: Antimicrobial peptides (AMPs) protect host from pathogens as first line of defense. Especially, β-defensins shows antimicrobial activity and immune modulation effects. Avian species also have β-defensins as avian β-defensins (AvBDs) from AvBD1 to AvBD14. In this study, we characterized chicken AvBD5 and demonstrated its immune modulatory functions in chicken macrophage cell line (HD11). Chicken AvBD5 is composed of a signal, pro, and mature peptides containing one α-helix, four β-sheet, and three disulfide bonds. Here, we also showed that chicken AvBD5 induced Th1, Th2, and Th17 cytokines in chicken macrophage cell line and stimulated MAPK signaling pathways through ERK1/2 and p38 molecules. In addition, AvBD5 stimulated MyD88 and CD40 to regulate immune systems. Taken together, chicken AvBD5 can modulate host immune systems by inducing cytokines expression and stimulating MAPK signaling pathway. Highlights: Chicken avian β-defensin 5 (AvBD5) induced Th1, Th2, and Th17 cytokines in chicken macrophage cell line (HD11). Chicken AvBD5 stimulated MAPK signaling pathways by phosphorylating ERK1/2 and p38 molecules. Chicken AvBD5 stimulated MyD88 and CD40 expression in chicken macrophage cell line.